Scientometric Study of Digital Transformation and Human Resources: Collaborations, Opportunities, and Future Research Directions - Pablo Reyes-Cornejo; Luis Araya-Castillo; Hugo Moraga-Flores; Joan Boada-Grau; César Olivares-Brito (Administrative Sciences)
While the importance of understanding digital transformation from a Human Resources (HR) perspective is widely acknowledged, a comprehensive analysis of the scholarly landscape remains limited. This study examines the scientific production on digital transformation and HR within the Web of Science database, analyzing bibliometric indicators of production, visibility, impact, and collaboration. The results reveal that digital transformation is a recent, relevant, and transdisciplinary construct that significantly influences talent management strategies and necessitates new skill sets within HR functions. This impact requires organizations to proactively develop digital skills, facilitating a regulated and controlled transition during the implementation of digital strategies. Specifically, organizations must focus on fostering employee adaptability and promoting work–life balance in this rapidly changing environment. Building on these findings, future research could benefit from employing mixed-methods approaches, combining quantitative bibliometric analysis with qualitative case studies to explore the contextual factors influencing the complex relationship between digital transformation and HR, such as organizational culture and leadership styles.